Accelerating social development through digital technology: Efforts to reduce urban-rural disparities within the framework of the 2030 SDGs - Herpita Wahyuni; Sanny Nofrima; Dwiki Adi Putra (Jurnal Sosiologi Dialektika, 2026)
To achieve the 2030 SDGs, this study will examine the acceleration of social development through the use of digital technology. This is done in an effort to reduce the disparity between urban and rural areas. Using qualitative methods and data analysis assisted by NVivo 12 Plus software, this study analyzes available digital infrastructure, digital literacy, access to services, and digital economic opportunities. The results show that digital infrastructure is a crucial component in equalizing access to information and public services. However, uneven availability remains a problem, especially in 3T (remote and underdeveloped) regions. Digital literacy in rural communities also needs to be strengthened so that technology can be optimally utilized to support improvements in quality of life. In addition, digital services such as e-government, digital payments, and e-commerce have been proven to open more efficient service access and new business opportunities for local MSMEs in supporting inclusive economic growth. However, this study has limitations in the scope of secondary data and does not include an in-depth field perspective. Therefore, further research is recommended to conduct a comprehensive analysis using mixed methods and expand the research object to different rural areas to obtain a more representative picture of the acceleration of digital transformation in Indonesia.